Indonesian L2 Learners’ CEFR-based Listening Proficiency: Interactions with Attitudes towards Teachers’ Use of L1 - Subekti, Adaninggar Septi; Widodo, Pratomo; Andriyanti, Erna (Acta Paedagogica Vilnensia, 2023)
The present study was conducted to investigate Indonesian second/foreign language (L2) learners’ self-rated CEFR-based listening proficiency (SR-CEFR-L) and the possible interaction with their attitudes towards teachers’ use of learners’ first language (L1), Indonesian, in English as L2 classes. 168 learners from non-English departments taking General English (GE) Levels 1, 2, and 3 participated in this survey study. Using the chi-square test of independence, this study found a significant difference among learners from different General English levels in their SR-CEFR-L, where the higher their GE levels the more likely they reported higher SR-CEFR-L. This study also found that generally, learners reported positive attitudes towards teachers’ use of L1 in English classes. This study further found no significant association between learners’ SR-CEFR-L and their attitudes towards teachers’ use of L1, suggesting that regardless of how highly they rated their listening proficiency, learners generally preferred their teachers using Indonesian in teaching English. From the findings, implications are suggested along with possible contributions and suggested directions for future studies in the field.